Development and validation of a human DNA quantification and sex determination approach based on real time PCR followed by high resolution melting analysis - Ginart, Santiago (2015)
DNA quantitation is one of the most crucial factors affecting the success and quality of DNA typing by PCR. The aim of this work was to develop a DNA quantification assay to be used in routine forensic casework. It should be able to discriminate, simultaneously, the presence of male and female DNA by means of multiplex real time PCR, followed by high resolution melting analysis (HRM), including a fluorescent intercalating dye Syto 9. The approach is co-amplified fragments of a gene common to both genders, Amelogenin-Amel and a specific sequence of the human Y chromosome (HSYCS) whose melting temperature differs from Amel in 5.3–5.5 °C. Hence, it allows discriminating two peaks after HRM analysis if only male DNA is present in the sample or a single peak if only female template is present. The short length of both amplicons, 106/112 bp for Amel and 84 bp for HSYCS, facilitates quantitation and gender detection in degraded samples that characterize evidentiary material. We achieved the quantification of male, female and experimentally mixed samples with very low DNA quantities (20 pg/μl). We propose an alternative approach to commercial DNA quantitation kits. Our development showed to be fast, highly sensitive, laborsaving and cost-effective.